Baicalin Alleviates Lipopolysaccharide-Induced Liver Inflammation in Chicken by Suppressing TLR4-Mediated NF-κB Pathway - Cheng, Ping; Wang, Tong; Li, Wei; Muhammad, Ishfaq; Wang, He; Sun, Xiaoqi; Yang, Yuqi; Li, Jiarui; Xiao, Tianshi; Zhang, Xiuying (Frontiers in Pharmacology, 2017)
As a kind of potent stimulus, lipopolysaccharide (LPS) has the ability to cause cell damage by activating toll-like receptor(TLR)4, then nuclear factor kappa B (NF-κB) translocates into the nucleus and changes the expression of related inflammatory genes. Baicalin is extracted from Radix Scutellariae, which possesses anti-inflammation, antioxidant and antibacterial properties. However, the effects of it on LPS-induced liver inflammation have not been fully elucidated. This study aims to investigate the anti-inflammatory effects of Baicalin on the LPS-induced liver inflammation and its underlying molecular mechanisms in chicken. The results of histopathological changes, serum biochemical analysis, NO levels and myeloperoxidase activity showed that Baicalin pretreatment ameliorated LPS-induced liver inflammation. ELISA and qPCR assays showed that Baicalin dose-dependently suppressed the production of IL-1β, IL-6 and TNF-α. Furthermore, the mRNA expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were significantly decreased by Baicalin. TLR4 is an important sensor in LPS infection. Molecular studies showed that the expression of TLR4 was inhibited by Baicalin pretreatment. In addition, Baicalin pertreatment inhibited NF-kB signaling pathway activation. All results demonstrated the protective effects of Baicalin pretreatmen against LPS-induced liver inflammation in chicken via negative regulation of inflammatory mediators through the down-regulation of TLR4 expression and the inhibition of NF-kB activation.